Antiretroviral Prescription and Viral Suppression in a Representative Sample of HIV-Infected Persons in Care in 4 Large Metropolitan Areas of the United States, Medical Monitoring Project, 2011–2013. (1st October 2017) - Wohl, Amy Rock; Benbow, Nanette; Tejero, Judith; Johnson, Christopher; Scheer, Susan; Brady, Kathleen; Gagner, Alexandra; Hughes, Alison; Eberhart, Michael; Mattson, Christine; Skarbinski, Jacek
Abstract : Background: Comparisons of antiretroviral therapy (ART) prescription and viral suppression among people in HIV care across US metropolitan areas are limited. Medical Monitoring Project, 2011–2013, data were used to describe and compare associations between sociodemographics and ART prescription and viral suppression for persons receiving HIV care. Setting: Chicago, Los Angeles County (LAC), Philadelphia, and San Francisco in the United States. Methods: Bivariate and multivariable methods were used. Results: The proportion of patients prescribed ART (91%–93%) and virally suppressed (79%–88%) was consistent although more persons were virally suppressed in San Francisco compared with the other areas, and a smaller proportion was virally suppressed in Philadelphia compared with Chicago. In the combined cohort, persons aged 30–49 years were less likely than persons 50+ (adjusted prevalence ratio (aPR) –0.97, confidence interval (CI): 0.94 to 0.99); persons reporting non-injection drug use were less likely than non-users (aPR = 0.94, CI: 0.90 to 0.98); and Hispanics were more likely than whites (aPR – 1.04, CI: 1.01 to 1.08) to be prescribed ART. Blacks (aPR = 0.93; CI: 0.87 to 0.99) and homeless persons (aPR = 0.87; CI: 0.80 to 0.95) were less likely to be virally suppressed in the combined cohort. In LAC, persons aged 30–49 years were less likely than those 50+ to be prescribed ART (aPR = 0.94, CI: 0.90 to 0.98). Younger persons (18–29) (aPR = 0.77; CI: 0.60 to 0.99) and persons with less than a high school education (aPR = 0.80; CI: 0.67 to 0.95) in Philadelphia, blacks (aPR = 0.90; CI: 0.83 to 0.99) and men who have sex with women only (aPR = 0.89; CI: 0.80 to 0.99) in Chicago, and homeless individuals in LAC (aPR = 0.80; CI: 0.67 to 0.94) were less likely to be virally suppressed. Conclusion: Data highlight the need to increase ART prescription to achieve viral suppression among younger persons, noninjection drug users, blacks, and homeless persons in US metropolitan areas and underscores the importance of region-specific strategies for affected subgroups.